Empowering ELT with ICT: Bridging Gender Gaps through Digital Innovation (Architecture Image Studies, 2025)
The study titled Empowering ELT with ICT: Bridging Gender Gaps through Digital Innovation explores the dynamic intersection of technology and inclusive language education, proposing a comprehensive and research-driven framework to assess, implement, and optimize the use of Information and Communication Technology (ICT) tools in English Language Teaching (ELT). In response to the growing demand for equitable and engaging learning environments particularly following the paradigm shifts caused by the COVID-19 pandemic. This investigation examines how ICT can be strategically utilized to bridge gender disparities in ELT classrooms carried out across three educationally significant districts in Andhra Pradesh—Guntur, Vijayawada, and Prakasam. The study employs a mixed-method approach, using a meticulously designed instrument to collect and interpret both quantitative and qualitative data. The key focus areas include the evaluation of digital learning platforms (such as LMS, video conferencing tools, collaborative apps, and language learning software), teacher and student readiness for ICT integration, institutional support structures, and perceptions of gender inclusivity in digital learning spaces. The methodological framework also incorporates adaptive feedback loops, localized policy recommendations, and scalable implementation models that enable tailored interventions based on regional educational needs. By examining how both male and female students interact with ICT tools, the study sheds light on access, usage patterns, and engagement levels, providing valuable insights into how digital resources can be leveraged to foster gender-equitable participation in ELT.Ultimately, the study offers a set of actionable strategies for educators, administrators, and policymakers aimed at creating technologically enriched, inclusive, and communicatively competent ELT environments. It positions ICT not merely as a supplementary teaching aid, but as a transformative force capable of democratizing language education and empowering learners of all genders with the skills and confidence needed for academic and real-world communication